Desvendando o microbioma bacteriano de Selaginella (Selaginellaceae, Lycopodiopsida) e Dirinaria (Caliciaceae, Ascomycota liquenizados) - MAYARA SANTANA ZANELLA (2024)
With the advancement of cultivation-independent techniques, it has become possible to conduct metagenomic analyses of microbial communities in various environments. Metagenomics involves the total extraction of DNA from an environment, allowing for analyses of microbial community diversity, functional potential, and taxonomy. Any organism can be studied through metagenomics, with the aim of understanding the bacterial community, its metabolites, and functions. Plants of the genus Selaginella are known for their unique structural classes of natural products and their wide range of biological effects. They are extensively studied in pharmacology due to the presence of secondary metabolites such as flavonoids, lignins, and selagelin analogs. Lichenized fungi are known for their symbiotic properties and the production of secondary metabolites, used as bioindicators of air quality. Despite the biotechnological potential of these two groups of organisms, little is known about the bacterial associations and their functions in Selaginella plants and lichenized fungi. This work aims to generate and discuss information about the composition, richness, and abundance of bacteria associated with two species of Selaginella (Lycopodiopsida, Selaginellaceae) and two species of lichenized fungi of the genus Dirinaria (Lecanoromycetes, Caliciaceae). To this end, populations from rural (Selaginella) and urban (Dirinaria) areas of Campo Grande, Mato Grosso do Sul, were selected. Metagenomic data were generated using the Ion Torrent platform (Gene Studio S5) and analyzed for diversity using the Qiime 2 program. The main bacterial phyla found in both species of Selaginella were Actinobacteria, Proteobacteria, and Chloroflexi, with the main representatives at the family level being Kouleothrixaceae, Pseudonocardiaceae, and Sphingomonadaceae. Root samples exhibited higher diversity indices compared to leaves, with Acidobacteria, Chloroflexi, and Verrucomicrobia being more prevalent in roots, while Cyanobacteria were predominantly found in leaves. No significant variations were observed when examining the same organ across different Selaginella species. For Dirinaria analyses, the bacterial community composition between the two species was marked by the prevalence of four phyla: Verrucomicrobia, Proteobacteria, Planctomycetes, and Actinobacteria. Additionally, bacterial populations residing on lichen thalli exhibited variance from those found on the substrate, suggesting a selective mechanism by the lichen for specific bacteria, presumably essential for its well-being and functionality.